Interest rate liberalization and the stability of the Chinese banking system: exploring chained mediation effects of deposit competitiveness and wealth management products - Kang, Kuan; Mohd Ashhari, Zariyawati; Yahya, Mohamed Hisham; Soh, Wei Ni; Li, Yue (Elsevier, 2024)
This study uses quarterly unbalanced panel data of 46 commercial banks and adopts a two-step system generalized method of moments to inspect the direct and indirect effects of interest rate liberalization (IRL) on banking stability from 2015 to 2021 in China. The results show that IRL enhances banking stability and brings deposit competition among banks, which affects banking stability. Meanwhile, wealth management products (WMPs) with higher market-based yields have increased dramatically as competitive substitution of deposits. The bootstrap test confirms the chained mediation effects of deposit competitiveness and WMPs development on the relationship between IRL and banking stability.